Action research on neglected and underutilized species. A methodological guide - Vernooy, Ronnie (2021)
This guide presents a systematic process to investigate, in a participatory manner, the current and potential roles of neglected and underutilized species, jointly with local communities. The process is divided in two major parts or phases: 1) Exploration; 2) Action learning.